Pengaruh Promosi dan Kualitas Produk Terhadap Keputusan Pembelian Smartphone Vivo dengan Brand Ambassador sebagai Variabel Moderasi - Ganendra, Johan Jaya; Yulia, Iis Anisa; Rumna (Jurnal EMT KITA, 2025)
This research aims to analyze the influence of promotion and product quality on purchasing decisions for Vivo smartphones with brand ambassadors as moderating variables. The sample used in this research was 135 respondents. Data was collected using a purposive sampling method and hypothesis testing using Moderated Regression Analysis (MRA). The results of this research show that Promotion has a significant influence on Purchasing Decisions and Product Quality has a significant influence on Purchasing Decisions, Brand Ambassadors can moderate the influence of Promotion and Product Quality on Purchasing Decisions.